Biodiversity of the alpine vascular flora of the N.W. North American Cordillera: the evidence from phyto-geography - Harris, Stuart A. (ERDKUNDE, 2007)
At the end of the Late Wisconsin glaciation, the alpine vascular flora had only about 3.5 ka in which to colonize the 1,600 km north-south extent of the formerly glaciated terrain in western Canada as soon as the ice melted, before the temperatures caused them to become isolated on individual mountains. This paper describes the source areas/refugia, and estimates the efficacy of the migration from each source. Basic data consists of details of the present-day vegetation from 29 alpine sites between the north coast of Alaska and Colorado. Over 70% of the alpine species in the Canadian Cordillera are only found on this continent. Distribution of individual species is sporadic, probably due to the short time available for colonization. Considerable speciation had occurred in each refugium during the glaciation, probably due to the greater success of mutations that could survive better than their parents in the new conditions. These new species allow the flora of each refugium to be identified. The ca. 629 species present were categorized into nine groups based on existing distributions. Plots of the percentages of species in each category produced maps showing that the species present in the Middle Cordilleran refugium in the vicinity of Plateau Mountain and on the Queen Charlotte Islands mainly migrated north and south along the adjacent mountain ranges. There was limited recruitment from the Southern Cordilleran species due to the wetter and colder conditions in the formerly glaciated terrain. New Beringian species showed mixed success, whereas the North Cordilleran, North American and Cordilleran species colonized the whole Cordillera in the available time. There was limited invasion of a few species from the adjacent Prairies. The results suggest that during repeated cold events, the alpine species can extend their ranges, becoming mixed to form the Cordilleran flora. The more plastic species with efficient dispersal mechanisms can spread and become part of the North American group. When the Bering Land Bridge is open, these species can then move to Eurasia, and have the potential to become part of the Circum-Subarctic group. However the number of species completing this process is small due to the time requirement, the inefficiency of dispersal, the overcoming of filters, and the availability of an open Bering Strait at a suitable time.